A comprehensive study of phytonematodes of grape plants in the conditions of the Surkhandarya Valley, Uzbekistan - ALISHER KHURAMOV; LOBAR BOBOKELDIEVA; SIROJ CHORIYEV; BAKHODIR RAKHMATULLAEV; NAVRUZ KHIMMATOV; SHAKHBOZ RAIMOV; GULCHEKHRA NARZULLAEVA; SHAKHNOZA BOBOKELDIYEVA; MUKHLISA MUKHIDDINOVA; MAKHBUBA KARSHIEVA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Khuramov A, Bobokeldieva L, Choriyev S, Rakhmatullaev B, Khimmatov N, Raimov S, Narzullaeva G, Bobokeldiyeva S, Mukhiddinova M, Karshieva M. 2024. A comprehensive study of phytonematodes of grape plants in the conditions of the Surkhandarya Valley, Uzbekistan. Biodiversitas 25: 4033-4042. Article analyzes the faunal complex of grape phytonematodes collected from 2018 to 2020 from 14 districts and 28 farms of the Surkhandarya Valley, Uzbekistan. Sample collection was carried out using the route (collecting samples by going to predetermined areas in a certain direction) method generally accepted in modern faunal studies. The Berman funnel method was used to isolate nematodes permanent and temporary preparations for determination of the type and gender of nematodes were prepared according to the Seinhorst method; when determining the species of phytonematodes, the works of domestic and foreign authors were used, as well as morphometric indicators obtained using the generally accepted de Mann formula. During the study period, we found 118 species of phytonematodes belonging to 54 genera, 33 families, 9 orders, and 2 subclasses on grape agrocenoses. The discovered nematodes are distributed among the orders as follows: The order Monhysterida is represented by 5 species: Enoplida-1, Mononchida-6, Dorylaimida-23, Alaimida-5, Rhabditida-7, Teratocephalida-25, Aphelenchida-19 and the order Tylenchida-27 species. The degree of dominance of registered phytonematodes in the roots and root soil of grapes was studied. According to the frequency of occurrence of the detected species of phytonematodes in root and soil samples, there were no dominant or eudominant species; in the root soil of grapes; of the subdominants 10 species and 108 species were classified as subrecedents. In the root system of grapes, the subdominants are total 10 species. In the root system of grapes, all other species of phytonematodes registered (74 species) are classified as subrecedents.